Architectural representations and the identity of Aceh: revisiting local tradition in modern time - Izziah; Dewi, Cut; Meutia, Erna (2024)
This paper explores architectural representation in Banda Aceh commissioned during Suharto's New Order. During this time, as Indonesian President Suharto encouraged Indonesians to raise the spirit of nationalism in search of local identity, like other places in Indonesia, the city of Banda Aceh witnessed the development of the built environment of Banda Aceh concerning the search for local identity. Concerning this, the paper focuses on how the modern architecture of Aceh deliberately incorporated traditional Acehnese elements. This paper focuses on the ideas of Ibrahim Hasan, a governor of Aceh during the New Order era between 1987 – 1993, who has tried to rethink the local identity of Aceh through several modern government buildings by revisiting its cultural tradition. As a result, in presenting the architectural identity of Aceh, the built form of Banda Aceh city sought to express traditional identity. Capitalizing on the rising sensitivity toward cultural tradition, the architectural representations appear to promote an eclectic trend of recollecting tradition; one is seen to be able to reclaim the identity of Aceh. In accomplishing this paper, the study conducts field observations and literature review. In doing this, the paper shows how the local government elites and architects working in Banda Aceh shared Suharto's view on creating a built environment that embraced traditional values. In addition, the paper also shows how they appropriate the global trend of regionalism while tracing its roots in the Western and Indonesian discourse of architecture.